Analisis Kinerja Organisasi Sektor Publik Dengan Metode Balanced Scorecard (Studi Kasus Pada Dinas Komunikasi Dan Informatika Provinsi Sumatera Utara) - Pratiwi, Anggun; Nurwani, Nurwani (JURNAL EKONOMIKA, 2022)
This study aims to analyze the performance of the Department of Communication and Information of North Sumatra Province as a public sector organization with a balanced scorecard approach. Performance is measured through four balanced scorecard perspectives, namely: financial perspective, internal business process perspective, growth and learning perspective, and customer/society perspective. The type of research used is descriptive qualitative research with data collection techniques through observation, interviews, questionnaires, and documentation. The results of this study indicate that performance appraisal from a financial perspective is economical with an average budget realization achievement of 86.60% in the past 3 years, which means it is effective and efficient, on the other hand, budget information is still not transparent. Performance appraisal from the community's perspective is considered good, the community is satisfied with relevant and updated information services. Performance appraisal according to the perspective of internal business processes is classified as efficient and good in providing services measured through several indicators. Performance appraisal based on learning and growth perspective is considered good considering the welfare of its employees as measured by several indicators.Keywords: Performance, Public Sector Organizations, Balanced Scorecard